Intraorbital, extraconal cavernous hemangioma: a common tumor at an uncommon site-a case report - Dr Sujata S. Giriyan; Dr Purushotham Reddy; Dr Deepti Dixit (Tropical Journal of Pathology and Microbiology, 2017)
A wide variety of processes can produce space occupying lesions in and around the orbit including benign neoplasms, malignant neoplasms, vascular lesions, inflammatory diseases, congenital lesions etc. Cavernous hemangioma is the most common benign non-infiltrative neoplasm of the orbit. It is also the most common intraorbital tumor found in adults.Although histologically benign, they can encroach on intraorbital or adjacent structures and be considered anatomically or positionally malignant. We present here a case of extraconal, intraorbital cavernous hemangioma in a 21 years old male diagnosed histopathologically. So, we conclude that even though intraorbital cavernous hemangiomas present most frequently at intraconal locations, extraconal site for its occurrence cannot be ignored and must be considered in evaluation of intraorbital vascular lesions.